PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA DE CONFECCIÓN Y COMERCIALIZACIÓN DE ROPA ANTIALÉRGICA PARA BEBÉS DE 0 A 6 MESES DE EDAD EN LA CIUDAD DE LOJA - Lanche Puchaicela, Yadira Elizabeth (2016)
He present work is performed with the purpose of make a "project of feasibility for the implementation of a company of making and marketing of clothing allergy for babies of 0 to 6 months of age, in the city of LOJA". For this reason intends to give parents an option for the care of their babies, as well as to also avoid allergic reactions or irritation, in its first six months of life, which is where more attention needs thus creates this new business idea which allows care baby that is delicate skin. This study carried out on the basis of four studies: market, technical, administrative and financial. For the achievement of them objectives, is used some materials and methods as: supplies of office, the team of computing, the method inductive for this project with the helps of them interviews and surveys personal, is attained generalize behaviors or skills between them consumers and suppliers of them rompers for babies, the method deductive is focused in the collection of data statistical which allowed make an analysis mathematical and of them data formulated in the instrument employee as were the encuestas. Se applied 384 surveys the plaintiffs of clothes for babies in which 69% have a baby understood at the age of 0 to 6 months; in what is refers to the survey applied to them suppliers exist in the city 41 local commercial dedicated to the sale of this product. The results of the market study were as follows: the potential demand for the year 0 amounts to 36.450 rompers baby, the real demand to 45.024; and the effective demand to 45.024. In terms of the offer for this year is 7.584 rompers baby, giving a 127.487 units unmet demand. 6 In the technical study which includes the size and location, the installed capacity was calculated the fraction of the capacity for the first year is 17,520 rompers; and in what is referred to the capacity used is produced 4.120 rompers to the year. However location made reference to the specific place where the Mamluks company, will be established will be located in the Centre of the city of Loja, in the streets of Lauro Guerrero between the Calle Miguel Riofrío and Azuay, equipped with basic services for the operation of the company. Continued to perform the administrative study, where the kind of company was detailed to become so-called company "Clothing Dayana", also raised organization charts and a manual functions likewise The results of the present study determined the feasibility of the project, according to financial indicators such as: the value Actual Net (VAN) is $5.131,60, in what refers to the internal rate of return is 24.39%; the Capital recovery period will retrieve it is in 1 year 0 months and 1 day, the benefit cost ratio that for every dollar invested company wins 0.39 cents of dollar, and sensitivity analysis costs may be increased by 13.73% and a decrease of 10.29% revenue which supports the project, which means with the information that the project is feasible. Determined the investment of the project, which is the amount of $24.420,36; that will be funded by the company the 91,73% and the 8,27%.por the Bank national of promotion. Finally, conclusions and recommendations of all of the investigative work, likewise bibliography, and finally the annexes are presented.